Padungku Sebagai Konsep Eklesiologi Pasca Konflik Poso dalam Hubungannya dengan Masyarakat Lintas Agama - Marsekal Gimbo; Imanuel Teguh Harisantoso (TEVUNAH: Jurnal Teologi dan Pendidikan Kristen, 2023)
This article analyzes how Padungku, an indigenous tradition of the Pamona tribe, became a concept of ecclesiology after the Poso conflict through the perspective of interfaith ecclesiology. The main problem in the Poso conflict is the clash between two different religious groups from each other so that all kinds of relationships of any kind between the two seem to be tightly closed, and there is no hope of opening up again. This paper uses a literature method to explore how Padungku became a new ecclesiological concept in the Poso community. The results found that through Padungku and the perspective of interfaith ecclesiology as aids, it will be seen that long-entrenched indigenous traditions played a role in unlocking all sorts of things that were not originally possible post-conflict. This openness is also inseparable from how its values are in line and accordance with ecclesial principles.